2018
DOI: 10.1016/j.fcr.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high temperatures in maize: Phenology and yield components

Abstract: Heat stress is a main threat to current and future global maize production. Adaptation of maize to future warmer conditions requires improving our understanding of crop responses to elevated temperatures. For this purpose, the same short-season (FAO 300) maize hybrid PR37N01 was grown over three years of field experiments on three contrasting Spanish locations in terms of temperature regime. The information complemented three years of greenhouse experiments with the same hybrid, applying heat treatments at var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 45 publications
15
144
1
2
Order By: Relevance
“…Increasing temperatures likely to be experienced under climate change demonstrate several negative effects plant growth and phenology. Lizaso et al [24] recorded a reduction of corn yield under field and controlled Corn -Production and Human Health in Changing Climate conditions owing to reduced pollen viability as impacted by increased temperatures. A critical knowledge gap under future climate scenarios will be to evaluate the interaction of high temperature and increased humidity on pollen survivability and the efficiency of the pollination process.…”
Section: Corn Productivity In Response To Climatementioning
confidence: 99%
“…Increasing temperatures likely to be experienced under climate change demonstrate several negative effects plant growth and phenology. Lizaso et al [24] recorded a reduction of corn yield under field and controlled Corn -Production and Human Health in Changing Climate conditions owing to reduced pollen viability as impacted by increased temperatures. A critical knowledge gap under future climate scenarios will be to evaluate the interaction of high temperature and increased humidity on pollen survivability and the efficiency of the pollination process.…”
Section: Corn Productivity In Response To Climatementioning
confidence: 99%
“…The observed variation in maize yield is the product of many interactive processes that make a mechanistic understanding of the drivers of this variation difficult. Throughout the life cycle of maize plants, yield is driven by biomass accumulation and partitioning between organs (Lizaso et al, ). Biomass accumulation can be expressed as growing season length (GSL) × average daily biomass growth rate (BGR).…”
Section: Introductionmentioning
confidence: 99%
“…(Mittler et al, 2012), but research in the field setting (in situ) is lacking. The majority of in situ HS studies conducted in maize have focused on evaluating and comparing genotypes, not on quantitative trait locus (QTL) mapping (Jodage et al, 2017;Akula et al, 2018;Lizaso et al, 2018). The lack of mapping studies is understandable, as heat waves are sporadic and of variable severity, making heat a difficult stress to study.…”
Section: Genetic Mapping Of Foliar and Tassel Heat Stressmentioning
confidence: 99%
“…In B73 ´ NC350, two tassel traits, tassel blasting and reduction in spikelet size, were scored at flowering. The majority of in situ HS studies conducted in maize have focused on evaluating and comparing genotypes, not on quantitative trait locus (QTL) mapping (Jodage et al, 2017;Akula et al, 2018;Lizaso et al, 2018). We previously observed that the development of leaf firing was differentiable between parents, and indeed, the different manifestations of the leaf firing trait were not significantly correlated and QTL did not co-localize.…”
Section: Introductionmentioning
confidence: 96%